Practical Resources for Talking to Children with Autism about Systemic Racism - Melendez, Julie L. (Behav Anal Pract, 2020)
As part of the child-rearing process, situations that invite difficult conversations will inevitably arise. Oftentimes, there are no guidelines or structure for how to discuss topics such as sex education, systemic racism, bullying, grieving, and gun violence. Accordingly, adults may feel at a loss for how to address difficult topics and may even avoid difficult conversations completely. When adults choose to have these conversations, they may imitate the conversations their caregivers had with them, and therefore further the cycle of systemic racism, often unknowingly and unintentionally. Racial injustice has been a core part of the American experience since the founding of the republic; hence, conversations about systemic racism are long overdue. The need has significantly increased, given the current socio-political climate. Social justice may be a sensitive topic for some, but it is a needed conversation for all, including children with Autism Spectrum Disorder (ASD). Currently available curricula and teaching manuals in the Applied Behavior Analysis (ABA) literature include little or no resources for caregivers on how to address systemic racism with their children on the spectrum. Children with ASD should be educated about how they, and their families, can combat systemic racism in their everyday lives. The present paper addresses this gap in available treatment resources by offering practical suggestions and guidelines for how adults can address the topic of systemic racism with children on the autism spectrum to educate them and prepare them to contribute to a more equitable and just future.